2016
DOI: 10.14238/sp17.1.2015.64-70
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kadar 25-Hydroksivitamin D dan High Molecular Weight Adiponectin pada Remaja Obes

Abstract: Latar belakang. Obesitas pada remaja berkaitan dengan obesitas dan morbiditas pada orang dewasa. Strategi preventif efektifmencegah perkembangan obesitas dan morbiditas masih terbatas. Hasil studi penilaian peran 25-hydroksivitamin D (25(OH)D)terhadap obesitas dan morbiditas yang diperantarai adiponektin masih inkonklusif. Saat ini, diketahui molekul HMW adiponektinbukan adiponektin total yang berkaitan erat dengan morbiditas obesitas.Tujuan. Mengetahui hubungan antara kadar 25(OH)D dan HMW adiponektin pada re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There was no interval range adiponectin for the adult population of Indonesia. 25 A total of 55% of subjects had abnormal level adiponectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no interval range adiponectin for the adult population of Indonesia. 25 A total of 55% of subjects had abnormal level adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…The result was consistent with the previous study that found CRP was increased significantly by the increase of BMI. 25,27 Enlarging and increasing adipocyte tissues in obesity are mediated by immuneassociated cells that increase proinflammation cytokines. 28 High CRP levels are related to the increased expression and release of IL-6 by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In Jakarta, vitamin D insufficiency in elementary school children was 75.9% and vitamin D deficiency was 15%. Vitamin D insufficiency in Manado, North Sulawesi, is 34%, while vitamin D deficiency is 64% in adolescents aged 10–18 years ( 23 ).…”
Section: Vitamin D Deficiency and Diseasesmentioning
confidence: 99%
“…Prevalence of vitamin D3 in Manado, North Sulawesi by 34% and vitamin D3 by 64% in adolescents aged 10-18 years. (Pangestu et al, 2016) Takumansang, Rifrita Fransisca Halim Vitamin D3 often occurs in patients with acute diarrhea. Research by Mahyar et al shows a significant relationship between Vitamin D3 serum and acute diarrhea.…”
Section: Introductionmentioning
confidence: 99%